Encirclement. Neo-Liberalism Ensnares Democracy - Brouillette, Richard (Les films du passeur production, 2008)
Verzio FF Submission Drawing upon the views of renowned professionals, this documentary sketches a portrait of neo-liberal ideology and examines its impact throughout the world. Among the contributors are Noam Chomsky, Ignacio Ramonet, Normand Baillargeon, Susan George, Omar Aktouf, Oncle Bernard, Michel Chossudovsky, François Denord, François Brune, Martin Masse, Jean-Luc Migué, Filip Palda and Donald J. Boudreaux.